Kultura organizacyjna szkoły integracyjnej w zwierciadle kultury pogranicza - Zenon Gajdzica, Zenon Gajdzica (Studia Edukacyjne, 2020)
The thesis is put forward in the presented article that the organizational specificity of integrated education creates a unique culture with some characteristics of typical borderland. Integrated school is a place where the dominating and the subordinated culture clash and/or collaborate. Depending on the precisely specified assumptions, beliefs, the recognized values and norms (consolidated within the institutional knowledge of a particular school), two different cultures of integrated school can be formed. These cultures are shaped by two types of social practices and two different models of the functioning of school. The study is aimed at a preliminary attempt to specify these models. They are assumed to comprise a set of notions which constitute analytical categories useful in describing the daily routine of school. Moreover, these models may become a tool for interpreting and understanding the states, processes and features of some elements of school and their interrelations.